PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK- TALK-WRITE UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA SISWA DI KELAS XI IPA 3 SMA NEGERI 12 MEDAN - HERNITA PURBA (JURNAL HANDAYANI PGSD FIP UNIMED, 2014)
ABSTRACT The research aims to look the students’ learning interest which disembogue on students’ learning activities while doing in grouping of class on subject of Indonesian language and increasing of students’ outcomes by applicated the learning model of Think-Talk-Write. This research subject was taken in class of XI IPA 3 SMA Negeri 12 Medan with number of 41 students. The initial teaching – learning process was done the learning outcomes test (Pretest), by the average of data is 33,4, that indicated the average of students seldom read the books before learning in school. Then, continued the teaching – learning process, the end of teaching – learning process II and IV is done the learning outcomes test for formative II and formative IV, which the result is indicated the average mark in formatif I is 65,4 and formatif II is 90,7. The data is seen that there is the changing, and the changing is affected teacher action during teaching – learning process in cycle I and II. The end of cycle II, is done the student learning interest assessment, the result is shown that comfortable attitude through Indonesian language lesson is 85,0, the student curiosity attitude through Indonesian language lesson is 82,0, and the attitude to help who have difficult in Indonesian language learning is 84,5. The student activites data accord the observer  observation on cycle I among others writing / reading  (36%), doing worksheet (31%), asking to friend (16%), asking to teacher (12%) and which not relevan (6%). Student activities data accord the observation on cycle II among others  writing / reading ( 25%), doing worksheet (38%), asking to friend ((20%), asking to teacher ( 17%), and not relevent with teaching – learning process (1%). The application of learning model of Think-Talk-Write during teaching – learning process make the student is happy, and enthusiastic.   Keywords: Cooperative learning model type Think-Talk-Write, learning interest, learning activities, learning outcomes